The Effect of THIEVES Strategy Towards Students’ Reading Comprehension in Recount Text - Ade Afriani; Hilma Pami Putri; Genta Sakti (Universitas Pahlawan Tuanku Tambusai, 2022)
This research was done because most of the students of Junior High School students still encounter problems in mastering English especialy reading comprehension in recount text. This research used experimental research. The researcher used a quasi experimental design by using the pre-test and post-test control group design. The population of this research was the eight grade students at SMPN 2 Kamang Magek. The sample was VIII.1 which was treated as experimental class and taught by using THIEVES strategy and VIII.2 was treated as control class and taught by using conventional strategy.The alternative hypothesis (Ha) was accepted which means that there is significant difference between using THIEVES strategy and conventional strategy. Then t-obtained both of classes in third hypothesis is (2.24) which was higher than t-table (1.6787) with (α)= 0,05. So, the alternative hypothesis (Ha) was accepted which means that THIEVES strategy is better than conventional strategy in teaching reading comprehension on recount text. So, it can be concluded that the entire hypothesis is accepted.